Long‐term follow‐up of haploidentical hematopoietic stem cell transplantation without in vitro T cell depletion for the treatment of leukemia. Issue 5 (23rd October 2012) - Wang, Yu; Liu, Dai‐Hong; Liu, Kai‐Yan; Xu, Lan‐Ping; Zhang, Xiao‐Hui; Han, Wei; Chen, Huan; Chen, Yu‐Hong; Wang, Feng‐Rong; Wang, Jing‐Zhi; Sun, Yu‐Qian; Huang, Xiao‐Jun
Abstract BACKGROUND: Many patients who require allogeneic hematopoietic stem cell transplantation (allo‐HSCT) lack a human leukocyte antigen (HLA)‐matched donor. Recently, a new strategy was developed for HLA‐mismatched/haploidentical transplantation from family donors without in vitro T cell depletion (TCD). METHODS: Over the past 9 years, 756 patients underwent haploidentical transplantation using a protocol developed by the authors, which combines granulocyte‐colony stimulating factor–primed bone marrow (G‐BM) and peripheral blood stem cells without in vitro TCD. The long‐term outcome with this treatment modality was reported, and a risk‐factor analysis was provided. RESULTS: Of these patients, 752 (99%) achieved sustained, full donor chimerism. The incidence of grades 2 through 4 acute graft‐versus‐host disease (GVHD) was 43%, and the 2‐year cumulative incidence of total chronic GVHD was 53%. The 3‐year cumulative incidence of nonrelapse mortality was 18%. The 2‐year cumulative incidences of relapse were 15% and 26% in the standard‐risk and high‐risk groups, respectively. Of the 756 patients, 480 survived throughout the follow‐up period of 1154 days (range: 335‐3511 days) with the 3‐year leukemia‐free survival rates of 68% and 49% in the standard‐risk and high‐risk groups, respectively. Lower leukemia‐free survival was associated with high‐risk disease status (P = .001), chronic myelogenous leukemia disease type (P = .004), neutrophil engraftment beyond 13 days after transplant (P = .012), and the occurrence of grades 2 through 4 acute GVHD (P = .019). CONCLUSIONS: The results from the authors' 9‐year experience showed that G‐BM combined with peripheral blood stem cells from haploidentical donors, without in vitro TCD, is a reliable source of stem cells for transplantation by using the protocol developed by the authors. Cancer 2013. © 2012 American Cancer Society.